Tanggung Jawab Pendidik Dalam Perspektif Islam - Mahfudzah, Fadhilatun (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
Educators should not cram students' brains with their own ideas or desires. Educators should raise the latent potential contained in students. In the first four years, children subconsciously absorb all ideas and feelings from their social environment. After that, in the next process he began to imitate the attitudes and ideas of the people around him. Here, educators and parents are required to set good examples in their daily behavior and actions, so that they become role models for students in a better direction. An educator should have adequate knowledge about the psychological development of students. This knowledge will really help him to get to know each individual student and make it easier to carry out the teaching and learning process.Â